2016
DOI: 10.11604/pamj.2016.25.72.6496
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia as a risk factor in the occurrence of stroke in Nigeria: prevalence and patterns

Abstract: IntroductionStroke is a major public health problem worldwide. Hypertension, diabetes mellitus, dyslipidaemia and smoking are some of the common modifiable risk factors in the occurrence of stroke. Therefore, this study was designed to assess the prevalence and patterns of dyslipidaemia among individuals with acute stroke.MethodsThis is a retrospective descriptive cross-sectional study, carried out in the Departments of Medicine at the LAUTECH Teaching hospital, Ogbomoso and General Hospital, Orile-Agege, Lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
5
20
2
3
Order By: Relevance
“…Africa (18.5%) [9]. Unlike many previous studies [22,30,38,[42][43][44][45], low HDL-C is the least prevalent component of dyslipidemia in this study. Advanced age, higher BMI, waking less than 150 minutes per week, raised FBG, and medium socio-economic status were significantly associated with a higher risk of dyslipidemia.…”
Section: Plos Onecontrasting
confidence: 66%
“…Africa (18.5%) [9]. Unlike many previous studies [22,30,38,[42][43][44][45], low HDL-C is the least prevalent component of dyslipidemia in this study. Advanced age, higher BMI, waking less than 150 minutes per week, raised FBG, and medium socio-economic status were significantly associated with a higher risk of dyslipidemia.…”
Section: Plos Onecontrasting
confidence: 66%
“…This finding is however in variance with other studies done among patients with diabetes2021 but similar to a study by Anyawu et al . and Olamoyegun et al ., who looked at endocrine-related disorders presenting to the Emergency in Lagos, Nigeria, and dyslipidemia in Nigerians, respectively 422. The higher percentage of patients with diabetes in our study (68.7%) is in keeping with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes mellitus had obvious impact on the lipids, which mainly reflects in the rise of Triglyceride (TG) and fall of High density lipoprotein cholesterol (HDL-C) [ 6 , 7 ]. Both the blood glucose and lipids would play the important role on the occurrence of arteriosclerosis, while lipids would play the more direct role [ 8 , 9 ]. Did this mean that the induction of arteriosclerosis and ischemic stroke by DM was through lipids, and this was proved in our previous study, that was, low level of HDL-C was correlated to the occurrence of AIS induced by DM [ 10 ], which demonstrated that dyslipidaemia was prone to happening in the AIS with DM.…”
Section: Introductionmentioning
confidence: 99%